A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 3. Revision of the Craspedophorus strachani and C. brevicollis groups (Coleoptera: Carabidae) - Häckel, Martin (Zootaxa, 2017)
Revised are Afrotropical species of the Craspedophorus strachani and C. brevicollis groups. New taxa are C. dicranulothorax n. sp. (Cameroon), C. lemariei n. sp. (Gabon), C. phenacoides n. sp. (Cameroon), C. ruficroides n. sp. (Guinea), C. cuneatus rotundatus n. ssp. (Cameroon, central Africa), C. ruficroides thomsoni n. ssp. (Cameroon, central Africa, Gabon), C. strachani bamendanus n. ssp. (Cameroon), C. tetrastigma morettoi n. ssp. (west Africa) and C. brevicollis beninensis n. ssp. (Benin). C. ruficrus (Laferté-Sénectere, 1851) and C. gabonicus (Thomson, 1858) are considered nomina dubia, because their original descriptions do not provide enough information to allow linking the names to any known specimens. To correct the situation, the authorship of C. ruficrus is ascribed to the first reviser, Chaudoir (1861) [as a valid name (sp. resurr.)], who designated a lectotype and provided an adequate redescription; the invalid name C. gabonicus (Thomson) sensu Chaudoir (1861) is synonymized with C. muata (Harold, 1883). The status of the following species is changed to subspecies: C. grossus (Hope, 1842) is demoted to ssp. of C. strachani (Hope, 1842), C. paromius Basilewsky, 1987 is demoted to ssp. of C. cuneatus (Alluaud, 1915) and C. milzi Duvivier, 1891 is demoted to ssp. of C. tetrastigma (Laferté). C. strachani depressus Burgeon, 1930 is synonymized with C. tetrastigma milzi Duvivier, 1891 and C. chevalieri jokoanus Basilewsky, 1987 is synonymized with C. chevalieri (Alluaud, 1915). C. strachani and C. brevicollis groups sensu Chaudoir 1879 are redefined. C. latemaculatus Alluaud, 1930 is removed from C. reflexus group Häckel 2016 and transferred to C. strachani group nov.